Acceptability and Feasibility of a Mobile Health Application for Video Directly Observed Therapy of Buprenorphine for Opioid Use Disorders in an Office-based Setting. Issue 4 (July 2020) - Godersky, Margo E.; Klein, Jared W.; Merrill, Joseph O.; Blalock, Kendra L.; Saxon, Andrew J.; Samet, Jeffrey H.; Tsui, Judith I.
Abstract : Introduction/Background: Video directly observed therapy (video-DOT) through a mobile health platform may improve buprenorphine adherence and decrease diversion. This pilot study tested the acceptability and feasibility of using this technology among patients receiving buprenorphine in an office-based setting. Methods: Participants were instructed to record videos of themselves taking buprenorphine. Data were collected from weekly in-person visits over a 4-week period; assessments included self-report of medication adherence, substance use, satisfaction with treatment and use of the application, and also urine drug testing. Open-ended questions at the final visit solicited feedback on patients' experiences using the mobile health application. Results: The sample consisted of 14 patients; a majority were male (86%) and White (79%). All participants except 1 (93%) were able to use the application successfully to upload videos. Among those who successfully used the application, the percentage of daily videos uploaded per participant ranged from 18% to 96%; on average, daily videos were submitted by participants 72% of the time. Most participants (10/14; 71%) reported being "very satisfied" with the application; of the remaining 4 participants, 2 were "satisfied" and 2 were "neutral." Participants reported liking the accountability and structure of the application provided and its ease of use. Negative feedback included minor discomfort at viewing one's self during recording and the time required. Conclusions: Based on these results, use of a mobile health application for video-DOT of buprenorphine appears feasible and acceptable for patients who are treated in an office-based setting. Further research is needed to test whether use of such an application can improve treatment delivery and health outcomes. Abstract : Supplemental Digital Content is available in the text